Current Practice of Informed Consent in Surgery Department at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: To determine the current preoperative informed consent practice in cases undergoing surgical procedures.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Surgery Department of PMC Hospital and PUMHS Nawabshah Sindh from Jan-2014 to April-2015.Materials and Methods: Following informed consent, 165 cases were incorporated in this study. Cases were randomly selected with suitable sampling technique and their surgical procedure was done electively, whereas those cases, which were treated conservatively and not capable of answering because of unconsciousness, eclampsia and shock, were not included in this study. Data was recorded on preplanned proforma concerning demographic information of cases, their knowledge regarding surgery carried out on them & the extent of data supplied them regarding risk, advantages of surgical procedure and other treatment choices.Results: Twenty nine (15%) cases were of age group of 20-35 yrs, whereas 104(53.88%) were of age group of 36-50 yrs. Well-versed consent was obtained from the cases by surgeon in 63(32.64%) cases, by inhabitants in 105(54.40%), house officers in 10(5.18%) and by nurses in 15(7.77%) cases. This was ensured from the records of patients. When/ the patients were inquired, weather they completely grasped the data given to them, 86(44.55%) declared “yes” whereas 107(55.44%) did not grasp the data offered to them.Conclusion: Our study concluded that the majority of our contributors were conscious regarding the surgery done on them however they were provided little facts about risk, complications & advantages of the surgery.